Reducing Math Anxiety in School Children: A Systematic Review of Intervention Research - Balt, Miriam; Börnert-Ringleb, Moritz; Orbach, Lars (Frontiers in Education, 2022)
Recent studies indicate that math anxiety (MA) can already be found in school-aged children. As early MA depicts a potential risk for developing severe mathematical difficulties and impede the socio-emotional development of children, distinct knowledge about how to reduce MA of school-aged children is of particular importance. Therefore, the goal of this systematic review is to summarize the existing body of research on MA interventions for children by identifying the approaches, designs, and characteristics as well as the effects of the interventions.